2015
DOI: 10.1530/jme-15-0100
|View full text |Cite
|
Sign up to set email alerts
|

miR-410 enhanced hESC-derived pancreatic endoderm transplant to alleviate gestational diabetes mellitus

Abstract: Gestational diabetes mellitus (GDM) is a condition commonly encountered during mid to late pregnancy with pathologic manifestations including hyperglycemia, hyperinsulinemia, insulin resistance, and fetal mal-development. The deficit and dysfunction of insulin secreting b-cells are signature symptoms for GDM. Pancreatic progenitors derived from human embryonic stem cells (hESCs) were shown to be able to effectively treat diabetes in mice. In this study, we first identified that microRNA-410 (miR-410) directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Cell culture experiments under normoxia and hypoxia conditions can elucidate the studies of EVs in vivo after acute exercise. In cell culture experiments, cardiomyocytes increased EVs release under hypoxia environment ( MacPherson et al, 2015 ; Mi et al, 2015 ). Therefore, part of the augmented concentration of EVs in rat serum after exercise could be a consequence of the reduction in the oxygen supply at the tissue level.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture experiments under normoxia and hypoxia conditions can elucidate the studies of EVs in vivo after acute exercise. In cell culture experiments, cardiomyocytes increased EVs release under hypoxia environment ( MacPherson et al, 2015 ; Mi et al, 2015 ). Therefore, part of the augmented concentration of EVs in rat serum after exercise could be a consequence of the reduction in the oxygen supply at the tissue level.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that miR-347a directly target LDHA in colorectal cancer cells [60]. MiR-410 represses LDHA expression and promotes embryonic stem cells (hESC) to differentiate into pancreatic endoderm (PE) in gestational diabetes mellitus treatment [61]. In our study, we showed that miR-34b-3 and miR-449a directly targeted LDHA and LDHA overexpression significantly recovered cell proliferation, LD content and LDH activity in NPC cells following transfection of miR-34b-3 and miR-449a.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-186 and miR-375 by chemical transfection of human iPSCs promoted islet-like cell cluster formation and induced β-cell lineage markers [113] . Furthermore, human embryonic stem cells with induced overexpression of miR-410 and miR-495, prior to differentiation into endoderm, led to improved glycemic control when transplanted in mouse models of gestational or T2D [114] , [115] . These studies demonstrate that miRNAs can direct developmental decisions and promote differentiation of distinct cell lineages and may be exploited therapeutically in stem-cell-based approaches aiming to replace differentiated endocrine cells for the treatment of diabetes.…”
Section: Mirna Therapeuticsmentioning
confidence: 99%